2003
DOI: 10.1038/ni1005
|View full text |Cite
|
Sign up to set email alerts
|

Mast cell–derived tumor necrosis factor induces hypertrophy of draining lymph nodes during infection

Abstract: Palpable swelling of regional lymph nodes is a common sequela of microbial infections but the mechanism responsible for the sequestration and subsequent coordination of lymphocyte responses within these dynamic structures remains poorly understood. Here we show that draining lymph nodes of mast cell-deficient mice did not demonstrate swelling after intradermal bacterial challenge. Testing of individual mast cell-derived products in this model indicated that tumor necrosis factor was the main mediator of nodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
230
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(249 citation statements)
references
References 40 publications
16
230
1
2
Order By: Relevance
“…In addition to local actions in the skin previous Wndings in mice show that as a result of dinitroXuorobenzene-induced contact hypersensitivity mast cells are activated and they migrate to draining lymph nodes wherein they can mediate T cell recruitment [198]. Further support for mast cellinduced lymph node activation and hypertrophy is provided by the study showing that activation of mast cells in mouse footpad by injection of Escherichia coli bacteria or compound 48/80 results in rapid draining of mast cell-derived preformed TNF to lymph nodes wherein it induces hypertrophy and recruitment of circulating T cells [115]. Further, Jawdat et al [81] have demonstrated that the mast celldependent lymph node activation in mice can be mast cell TNF-dependent in an allergic response or TNF-independent in a response to bacterial peptidoglycan injection.…”
Section: Mast Cells In Relation To Cells Of the Immune System In Psormentioning
confidence: 74%
“…In addition to local actions in the skin previous Wndings in mice show that as a result of dinitroXuorobenzene-induced contact hypersensitivity mast cells are activated and they migrate to draining lymph nodes wherein they can mediate T cell recruitment [198]. Further support for mast cellinduced lymph node activation and hypertrophy is provided by the study showing that activation of mast cells in mouse footpad by injection of Escherichia coli bacteria or compound 48/80 results in rapid draining of mast cell-derived preformed TNF to lymph nodes wherein it induces hypertrophy and recruitment of circulating T cells [115]. Further, Jawdat et al [81] have demonstrated that the mast celldependent lymph node activation in mice can be mast cell TNF-dependent in an allergic response or TNF-independent in a response to bacterial peptidoglycan injection.…”
Section: Mast Cells In Relation To Cells Of the Immune System In Psormentioning
confidence: 74%
“…In many of these studies, the end points assessed included the recruitment of particular immune cells, such as granulocytes 28,32,33,[57][58][59][60][61]63,64,[67][68][69][70] , DCs 62,64,65,71 or various subpopulations of lymphocytes 64,67,70,72 . Many of these studies also demonstrated that the lack of mast cells 54,[57][58][59][60][61][62][63][64]67,69,70 or a specific mast-cell product 28,32,33,54,60,63,67,68,70 also reduced the pathology associated with the immune response or impaired its effectiveness in promoting host resistance to infection.…”
Section: Positive Immunomodulatory Functions In Vivomentioning
confidence: 99%
“…A study by Alard et al (19) suggested that mast cell-derived TNF might inhibit contact sensitization through effects on dendritic cells in mice. A recent report has also demonstrated that mast cell-derived TNF is primarily responsible for LN swelling following bacterial or compound 48/80-induced mast cell activation (20), while histamine did not contribute significantly to this response. Dendritic cells have, however, been shown to express H1, H2, and H3 receptors and to undergo significant maturational changes as a result of histamine treatment (11,(21)(22)(23).…”
mentioning
confidence: 99%